2023
DOI: 10.1002/nop2.2000
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment and quality of life in haematopoietic stem cell transplantation patients: A quantitative study

Marija Turlinskienė,
Raminta Seniūnaitė‐Ramanauskienė,
Justina Pociūnaitė
et al.

Abstract: AimThis study aimed to evaluate the relationship between psychological empowerment, depression, anxiety, and quality of life in people with haematopoietic stem cell transplantation (HSCT).DesignA longitudinal prospective study.MethodsA sample of 150 people with haematological was recruited at Santaros Clinics in Lithuania between September 2020 and April 2022. Demographic characteristics, cancer‐related characteristics, depression, anxiety, psychological empowerment and quality of life (QoL) were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(73 reference statements)
0
0
1
Order By: Relevance
“…In the present study, we found that the detection rate of anxiety and depression in 275 HSCT patients was 38.5%, with severity ranging from mild to moderate, which was higher than the ndings of Noyan et al [4]. Turlinskienė's report stated that women were more prone to depression after HSCT compared to men [13].…”
Section: Multifactorial Analysis Of Factors Affecting Anxiety and Dep...contrasting
confidence: 66%
“…In the present study, we found that the detection rate of anxiety and depression in 275 HSCT patients was 38.5%, with severity ranging from mild to moderate, which was higher than the ndings of Noyan et al [4]. Turlinskienė's report stated that women were more prone to depression after HSCT compared to men [13].…”
Section: Multifactorial Analysis Of Factors Affecting Anxiety and Dep...contrasting
confidence: 66%